2020
DOI: 10.1177/0898264320983663
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Multimorbidity among Cisgender Sexual Minority and Heterosexual Adults: Investigating Differences across Age-Groups

Abstract: Objectives: Despite increased risk for chronic disease, there is limited research that has examined disparities in multimorbidity among sexual minority adults and whether these disparities differ by age. Methods: Data were from the 2014–2018 Behavioral Risk Factor Surveillance System. We used sex-stratified multinomial logistic regression to examine differences in multimorbidity between sexual minority and heterosexual cisgender adults and whether hypothesized differences varied across age-groups. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 73 publications
0
7
1
Order By: Relevance
“…Fifth, the analyses were performed separately based on the indicated sex, but information on sexual orientation was missing. However, multimorbidity was found to be increased among sexual minorities [122,123], and respective effects could not be considered in the present study. Finally, this study focused on the comorbidity of two conditions, although multimorbidity is a common phenomenon for many patients.…”
Section: Limitationscontrasting
confidence: 66%
“…Fifth, the analyses were performed separately based on the indicated sex, but information on sexual orientation was missing. However, multimorbidity was found to be increased among sexual minorities [122,123], and respective effects could not be considered in the present study. Finally, this study focused on the comorbidity of two conditions, although multimorbidity is a common phenomenon for many patients.…”
Section: Limitationscontrasting
confidence: 66%
“…In addition, we found that older adults in the present study who identified as “something else” were more likely to also identify as Latino. Prior work has demonstrated that individuals who identify their sexual identity as “something else” have distinct health behaviors and risks compared to gay/lesbian, bisexual, and heterosexual adults (Caceres, Travers, & Sharma, 2021; Eliason et al, 2016; Martinez et al, 2017). This warrants further investigation into the health needs of this unique group.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is growing evidence that individuals who identify their sexual identity as “something else” or “other” are more likely to report lower incomes than heterosexual adults (Caceres, Travers, & Sharma, 2021; Caceres, Turchioe et al, 2021; Martinez et al, 2017). Most relevant to the HRS sample, analyses of data from the Behavioral Risk Factor Surveillance System found that older adult participants were more likely than younger participants to indicate their sexual identity was something other than heterosexual, gay/lesbian, or bisexual (Caceres, Travers, & Sharma, 2021). Eliason et al (2016) assert that most sexual minority researchers analyzing population-based data have excluded the category of “something else” in their analyses (Eliason et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Though the potential role mindfulness programs can play in chronic disease management has gained recognition, these interventions often target specific diseases and either patients or caregivers rather than addressing the broader needs of individuals managing multiple chronic diseases and roles (i.e., caregiver and patient). 21,22 In the US, disproportionately higher rates of many chronic diseases and a higher prevalence of multi-morbidity have been reported within populations marginalized due to factors such as race/ethnicity, 23 gender and sexual orientation, 24 education, and socioeconomic status. 25,26 These populations are also underrepresented in research on mindfulness interventions.…”
Section: Introductionmentioning
confidence: 99%